Argentinian National Intelligence: Functionality and Budget. Its Impacts on Intelligence culture (1989-2022) - Vitti, Jorge Gabriel (FLACSO - Sede Ecuador, 2022)
Intelligence is an indispensable tool for making strategic decisions. However, it is not perceived as such by broad sectors of Argentinian society. This work explores some of the most important foundations of the absence of intelligence culture, in a relevant period due to several serious events, to determine the existence of normative bases and their correct application in specific situations. To this end, the most significant aspects of that vision are explored, delving into both the doctrine and the regulations, as well as their application and impact: its public function, closely related to the perception of the usefulness and effectiveness of its services; and the allocation and use of earmarked budget expenses. Finally, conclusions and strategies for the construction of a culture of national intelligence, within the framework of a rule of law are presented.